Proceedings of the Twenty-Eighth International Joint Conference on Artificial Intelligence 2019
DOI: 10.24963/ijcai.2019/527
|View full text |Cite
|
Sign up to set email alerts
|

Tag2Gauss: Learning Tag Representations via Gaussian Distribution in Tagged Networks

Abstract: Keyword-based tags (referred to as tags) are used to represent additional attributes of nodes in addition to what is explicitly stated in their contents, like the hashtags in YouTube. Aside of being auxiliary information for node representation, tags can also be used for retrieval, recommendation, content organization, and event analysis. Therefore, tag representation learning is of great importance. However, to learn satisfactory tag representations is challenging because 1) traditional representation methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…On the other hand, adversarial perturbations on model parameters demonstrates an entirely new paradigm of adversarial training and shows great potential in promoting model effectiveness, especially for those solving transductive embedding problems. A reasonable explanation is in urgent need to exhibit why and where APP can work well, and thus we are able to determine whether APP can be generalized to other similar scenarios such as word embedding [25,30], tag embedding [45,47], table embedding [13,18,52] and broader domains.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, adversarial perturbations on model parameters demonstrates an entirely new paradigm of adversarial training and shows great potential in promoting model effectiveness, especially for those solving transductive embedding problems. A reasonable explanation is in urgent need to exhibit why and where APP can work well, and thus we are able to determine whether APP can be generalized to other similar scenarios such as word embedding [25,30], tag embedding [45,47], table embedding [13,18,52] and broader domains.…”
Section: Introductionmentioning
confidence: 99%
“…Graph, as a general data structure to represent relationships between entities, is ubiquitous in the real world. Many of them are temporal graphs that are dynamic and evolving over time [3,21], such as E-commerce networks, social networks and communication networks [13,15]. In such real graphs, one popular demand is temporal link prediction which is to predict new links in the future according to the historical information, such as recommending products to users in E-commerce networks, recommending friends to users in social networks, etc [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…† Corresponding Authors. 1 CIKM19 Best Research Paper Runner-up Award found in the social network of animals, and category hierarchy is widely used in lots of e-commerce sites (e.g., Alibaba, Amazon and Rakuten Ichiba) [11,12,13]. "Women's Fashion → Tops → Sweaters → Longsleeved knit → Crew neck" is an example of such an organization.…”
Section: Introductionsmentioning
confidence: 99%